The Role of Peroxisome Proliferator-Activated Receptors in Pulmonary Vascular Disease - Rachel E. Nisbet; Roy L. Sutliff; C. Michael Hart (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors belonging to the nuclear hormone receptor superfamily that regulate diverse physiological processes ranging from lipogenesis to inflammation. Recent evidence has established potential roles of PPARs in both systemic and pulmonary vascular disease and function. Existing treatment strategies for pulmonary hypertension, the most common manifestation of pulmonary vascular disease, are limited by an incomplete understanding of the underlying disease pathogenesis and lack of efficacy indicating an urgent need for new approaches to treat this disorder. Derangements in pulmonary endothelial-derived mediators and endothelial dysfunction have been shown to play a pivotal role in pulmonary hypertension pathogenesis. Therefore, the following review will focus on selected mediators implicated in pulmonary vascular dysfunction and evidence that PPARs, in particular PPARγ, participate in their regulation and may provide a potential novel therapeutic target for the treatment of pulmonary hypertension.